Detoksifikasi Instagram Sebagai Upaya Penyelesaian Kecemasan Komunikasi Pengguna - Vincentius Raditya Kristiawan; Wiwid Noor Rakhmad (Interaksi Online, 2021)
The ‘Instagram detoxification’ phenomenon is a proof that Instagram has negative impacts on its users, so that users decide to stop using it for a moment. One of the negative impacts experienced is communication apprehension. This research aims to describe the communication apprehension that comes from daily use of Instagram, as well as to explain the communication apprehension experienced by someone that went through Instagram detoxification using qualitative research methods and an interpretive paradigm with a phenomenological approach. This study uses in-depth interviews as a data collection technique. The theory used in this research is Communication Apprehension Theory. The result shows that communication apprehension appears when users experience feelings of fear, insecurity, jealousy, sadness, and start to compare themselves with others, which is caused by new things in certain communication situations, lower status compared to others, as well as differences that occur in an interaction, and the differences between individual’s personal traits with new things in his environment. Instagram detoxification is a form of external effect from communication apprehension, namely withdrawal patterns. Instagram detoxification brings changes to an individual with communication apprehension such as being calmer, more grateful, ready to see Instagram from a different perspective, better prepared to face various feelings that will arise due to Instagram use, more productive and accepting of the conditions that are being experienced.